The evolution of leukaemia from pre‐leukaemic and leukaemic stem cells. (29th January 2021) - Shlush, L. I.; Feldman, T.
Abstract: Haematopoietic stem and progenitor cells (HSPCs) are defined as unspecialized cells that give rise to more differentiated cells. In a similar way, leukaemic stem and progenitor cells (LSPCs) are defined as unspecialized leukaemic cells, which can give rise to more differentiated cells. Leukaemic cells carry leukaemic mutations/variants and have clear differentiation abnormalities. Pre‐leukaemic HSPCs (PreL‐HSPCs) carry pre‐leukaemic mutations/variants (pLMs) and are capable of producing mature functional cells, which will carry the same variants. Under the roof of LSPCs, one can find a broad range of cell types genetic and disease phenotypes. Present‐day knowledge suggests that this phenotypic heterogeneity is the result of interactions between the cell of origin, the genetic background and the microenvironment background. The combination of these attributes will define the LSPC phenotype, frequency, differentiation capacity and evolutionary trajectory. Importantly, as LSPCs are leukaemia‐initiating cells that sustain clinical remission and are the source of relapse, an improved understanding of LSPCs phenotype would offer better clinical opportunities for the treatment and hopefully prevention of human leukaemia. The current review will focus on LSPCs attributes in the context of human haematologic malignancies. Abstract : Content List ‐ 16th Key symposium: "The origin of cancer"